Development and validation of a questionnaire to assess women’s hookah smoking: insights from a multi-stage study - Nahid Shahabi; Azin Alavi; Shirin Shahbazi Sighaldeh; Sara Dadipoor; Shokrollah Mohseni; Hadi Eshaghi Sani Kakhaki; Ziyad Ben Talebh; Ebbie Kalan (BMC Public Health)
Abstract Background of study Hookah smoking is a major concern worldwide, especially in Eastern Mediterranean countries. In this study, we aimed to develop and psychometrically test the factors underlying hookah smoking among women. Methods We conducted both qualitative and quantitative phases between 2019 and 2022. The study sample comprised women who smoked hookah and were visiting health centers in Bandar Abbas. The primary questionnaire items were developed based on the findings from the qualitative phase of the study. The validity of the questionnaire was tested using the item impact, content validity ratio (CVR), content validity index (CVI), and face validity. A total of 485 subjects completed the questionnaire for an exploratory factor analysis (EFA) and 485 subjects did so for a confirmatory factor analysis (CFA). Results In the qualitative phase, 97 items were generated to enter the psychometric phase. Twelve items were removed based on the content validity results and six were removed in the face validity phase. In the EFA, 16 items were removed with factor loadings less than 0.3, and 81 items were loaded on 16 factors. CFA results of the 16-factor structure of the questionnaire included socio-economic deficiencies, role of advertisement and education, availability, fun and entertainment, hookah smoking in family and relatives, search for peace, others’ attention and approval, physical/mental dependence, color, flavor and sound of hookah, happy environment of coffee shops, pleasant experience of the first puff of hookah smoking, more acceptability of hookah smoking in society (vs. cigarettes), false beliefs, low self-efficacy, peer pressure, and family tendencies. Conclusion This study provides a robust, reliable, and valid tool to identify the complex social, psychological, and environmental factors driving hookah smoking among women in Iran. The findings underscore the urgent need for tailored, multi-pronged public health interventions to curb this emerging global health threat.